Strategi Pencegahan dan Penanggulangan Terjadinya Karat pada Geladak Utama di Kapal MV. Latifah Baruna - Alfando Tauqit Mahendra; Retno Indriyati; BL.Hentri Widodo (Politeknik Bumi Akpelni Semarang, 2025)
Rust on the main deck of a ship is a serious problem that can disrupt the safety and operational performance of the ship. The MV. Latifah Baruna, which operates in waters with tropical climate conditions, faces challenges related to rust on the main deck that has the potential to accelerate damage to the ship's structure. This problem is often caused by environmental factors such as high humidity, drastic temperature changes, and exposure to salty seawater. The impact of this rust not only reduces the durability of the ship's structure, but also has the potential to increase significant maintenance costs. The analysis methods used in this study include observations of the condition of the ship's main deck, interviews with related parties, and literature or documentation studies.The analysis focuses on the implementation of effective preventive strategies, such as maintaining the strength of the ship's construction structure, routine maintenance and cleaning, and temperature and humidity control. In addition, countermeasures against rust that has occurred through structural repair techniques are also discussed to ensure the integrity of the ship's main deck is maintained, such as preventing the recurrence of rust, cleaning and removing rust, and using rust converters. And main deck maintenance is carried out by knowing the level of crew safety, cleanliness and regularity conditions, and maintenance and care of the main deck. The conclusion of this study shows that the implementation of a comprehensive preventive strategy and routine monitoring of the condition of the ship's main deck can reduce the potential for damage due to rust. The use of rust-resistant materials, as well as training the ship's crew in preventive maintenance are also key factors in reducing maintenance costs and increasing the life of the ship.